Pengaruh Lingkungan Kerja dan Kompetensi terhadap Kinerja Karyawan melalui Motivasi Kerja pada Karyawan PT Pegadaian Cabang Blitar - Ayu Wahyuni; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to analyze the performance of employees. This study uses the variables of work environment, competency and work motivation to analyze the effect on employee performance. The population used is 31 employees using a questionnaire method by providing a list of questions directly to the respondents. The sampling method uses a total sampling method where the entire population in the study is sampled. The data analysis technique in this study uses SEM (Structural Equation Modeling) analysis which is operated through the Partial Least Square (PLS) program. The results of this study found that the work environment and competency has a significant effect on employee performance, work motivation has no significant effect on employee performance, meaning that the higher the influence of work motivation then does not affect on employee performance. The work environment has no significant effect on work motivation, competency has a significant effect on work motivation, indirectly the work environment through motivation has an insignificant influence on performance, and indirectly competency through motivation has an insignificant effect on the performance employees.